1992
DOI: 10.1111/j.1530-0277.1992.tb01396.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Brain Polyribosomal RNA Translation and Lymphocyte Proliferation in Prenatal Ethanol‐Exposed Rats

Abstract: The long-term effects of prenatal ethanol exposure on the properties of brain polysomes and the proliferative responses of lymphocytes to mitogenic stimulation in adult offspring were assessed. Female Sprague-Dawley rats either ingested the control or 6.6% ethanol-containing Lieber-DeCarli liquid diet during the 3rd trimester of pregnancy. Controls were age-matched and pair-fed. At 42 to 72 days of age, ethanol effects were evaluated on the (1) polysomal properties in the cerebral hemispheres, cerebellum, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Major cellular sources of IL-10 are macrophages and T-cells (mainly T-helper 1/Th1 and regulatory T/Treg) [51,82] that infiltrate the sciatic nerve and DRG following CCI [88]. Interestingly, a number of studies show PAE alters cell-mediated immune responsiveness, as demonstrated by reduced proliferative responses of splenic or thymic T-cells [40,41,76,101]. However, this effect varied on the timing and extent of ethanol exposure [10,70,76].…”
Section: Discussionmentioning
confidence: 99%
“…Major cellular sources of IL-10 are macrophages and T-cells (mainly T-helper 1/Th1 and regulatory T/Treg) [51,82] that infiltrate the sciatic nerve and DRG following CCI [88]. Interestingly, a number of studies show PAE alters cell-mediated immune responsiveness, as demonstrated by reduced proliferative responses of splenic or thymic T-cells [40,41,76,101]. However, this effect varied on the timing and extent of ethanol exposure [10,70,76].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should also be noted that studies using high doses of ethanol can be confounded by significant changes in neurological and behavioral function (Tewari et al. ), which may in turn affect cardiovascular function.…”
Section: Discussionmentioning
confidence: 99%
“…Given the disparity in our findings compared to other studies, in future studies it would be beneficial to conduct a study where the dams consume varying doses of ethanol to examine the dose effects. However, it should also be noted that studies using high doses of ethanol can be confounded by significant changes in neurological and behavioral function (Tewari et al 1992), which may in turn affect cardiovascular function.…”
Section: Discussionmentioning
confidence: 99%